Crystal Structures and Spin‐Crossover Behavior of Iron(II) Complexes with Chiral and Racemic Ligands. Issue 7 (8th February 2017) - Sekimoto, Yusuke; Karim, Mohammad Razaul; Saigo, Naoto; Ohtani, Ryo; Nakamura, Masaaki; Hayami, Shinya
Abstract : Chiral iron(II) complexes, [Fe( R )‐L2 (NCS)2 ] (1 ) and [Fe( S )‐L2 (NCS)2 ] (2 ), and racemic complex [Fe( rac )‐L)2 (NCS)2 ] (3 ) L = α‐methyl‐ N ‐(2‐pyridinylmethylene)cyclohexanemethanamine were synthesized. Their structures and magnetic properties were investigated by X‐ray crystallography, magnetic susceptibility measurements, and Mössbauer spectroscopy. Complexes1 and2 crystallize in the trigonal system with space group P 31 21 and P 32 21, respectively. All complexes exhibit spin‐crossover (SCO) behavior and light induced excited spin state trapping (LIESST) effects at 532 nm. Complexes1 and2 show similar gradual SCO behavior, and complex3 shows more gradual SCO, which seems to be a result of the different crystal packing, as complex3 is the symmetric isomer but1 and2 are asymmetric. Abstract : Chiral complexes [Fe( R )‐L2 (NCS)2 ] and [Fe( S )‐L2 (NCS)2 ] and racemic complex [Fe( rac )‐L2 (NCS)2 ], where L = N ‐(1‐cyclohexylethyl)‐1‐(pyridin‐2‐yl)methanimine, exhibit spin‐crossover (SCO) behavior and light induced excited spin state trapping (LIESST) effects.